2013
DOI: 10.1111/jssr.12066
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement and Religion Online: Stillbirth, Neonatal Loss, and Parental Religiosity

Abstract: Stillbirth and neonatal death often trigger immense and long‐lasting grief in parents. These life‐altering losses both call upon and call into question parents’ religious beliefs and practices. This qualitative research examines the impact of stillbirth and neonatal death on parental religiosity, broadly conceived to include personal spirituality and any religious affiliation, including atheism. It examines religion online, a nontraditional but important social context for grief, especially regarding statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
20
0
3
Order By: Relevance
“…These activities provide the mothers with the discussion they reportedly want and need. This suggests that bereaved mothers valued the social support received from family and friends and used non-religious activities to relieve feelings of hopelessness, sadness and loneliness, to connect with their inner self, to acknowledge their strengths and ultimately find peace (Bakker & Paris, 2013). Additionally, studies of gender differences in bereaved couples' grief reaction have found mothers to have a longer recovery time in adjusting to their grief than fathers (Armentrout, 2009; Lang, Gottlieb, & Amsel, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities provide the mothers with the discussion they reportedly want and need. This suggests that bereaved mothers valued the social support received from family and friends and used non-religious activities to relieve feelings of hopelessness, sadness and loneliness, to connect with their inner self, to acknowledge their strengths and ultimately find peace (Bakker & Paris, 2013). Additionally, studies of gender differences in bereaved couples' grief reaction have found mothers to have a longer recovery time in adjusting to their grief than fathers (Armentrout, 2009; Lang, Gottlieb, & Amsel, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Some felt that God was punishing them; others questioned or abandoned their belief in a perfect omniscient and omnipotent God, instead choosing to believe in a higher power that can make mistakes (Armentrout, 2009; Bakker & Paris, 2013). Meert et al (2005) found that 30 to 60% of bereaved parents expressed anger and blame at themselves and God for their infant's/child's death.…”
Section: Use Of Spirituality/religion As a Coping Strategymentioning
confidence: 99%
“…Bereaved parents also may question their religious and spiritual beliefs during this time of crisis. Bakker and Paris (2013) explored the use of religion as a coping strategy by 148 bereaved parents who participated in an online message board for pregnancy and neonatal loss. Most participants were females (96%) and their ages ranged from 20s to early 40s.…”
Section: Religion/spiritual Beliefs and Bereavementmentioning
confidence: 99%
“…Damage to a couple's relationship in the wake of the loss may also bring about a different meaning reconstruction. Finally, the literature suggests that religious affiliation can affect the perception of this loss ( Bakker & Paris, 2013). Future studies should approach a more heterogeneous population and encompass professionals and family members, as well.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies concerning women who have experienced SB-albeit not necessarily with a focus on the process of meaning reconstruction-have found that they do undergo this process. ( Bakker & Paris, 2013;Gilbert & Smart, 1992;Willick, 2006). In 1983, for example, Lovell argued that for women who experience SB, the environment's denial of the identity of the lost figure as a baby and the women's identities as mothers can induce women to make those rejections, themselves.…”
Section: Present Studymentioning
confidence: 99%